Situating case-based learning among other learning-centric pedagogies - Dobozy, Eva (Libri Publishing, 2014)
The proliferation of meanings of case-based learning (CBL), case-based teaching (CBT) or simply learning and teaching with case studies (CS), and the often confusing mix between CBL/T and problem-based learning (PBL) or inquiry-based learning (IBL), necessitates an attempt to situate CBL and other action-based and experiential approaches to learning and teaching within the learning-centric pedagogical landscape. Moreover, it demands clarity about the definitional constructs used within this chapter. Hence, I will commence with a definition of the noun Definition, which is, according to the Oxford Dictionaries (2013;1) "a statement of the exact meaning of a word", with the sole purpose to get to the essence of an object, notion or concept. In the case of situating CBL among other learning-centric pedagogies, the aim is to establish boundaries, scope, characteristics and limits of CBL before exploring aspects of its history, philosophy, and relational alliances with other learning-centric models of education The parts of what I call the learning-centric pedagogical model of contemporary education include, but are not limited to, learning and teaching strategies introduced here.